2012
DOI: 10.1007/s12011-012-9525-3
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Iron Status and Oxidative Stress in Patients with Metabolic Syndrome

Abstract: Studies concerning oxidative stress (OxE) parameters have increased, mainly because of its important role in cardiovascular diseases and diabetes complications. The main objective of this study was to evaluate iron nutrition status and oxidative stress parameters in subjects that had developed metabolic syndrome (MetS). Subjects from the Research Program of Risk Factors for Cardiovascular Disease (n = 155) were studied (ages ranging from 45 to 65 years old) and classified according to the Adult Treatment Panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 40 publications
0
27
0
1
Order By: Relevance
“…The participants with higher risks for MetS had the highest serum ferritin quartile compared with those with the lowest. However, the association study of body iron status and oxidative stress factors with MetS described that individuals with MetS presented low TfR, despite the increase of plasma ferritin [29]. Also, individuals with an abdominal adiposity component of MetS showed higher levels of sTfR, although sTfR presented no significant difference between participants with or without MetS in the population based case control study [7].…”
Section: Discussionmentioning
confidence: 91%
“…The participants with higher risks for MetS had the highest serum ferritin quartile compared with those with the lowest. However, the association study of body iron status and oxidative stress factors with MetS described that individuals with MetS presented low TfR, despite the increase of plasma ferritin [29]. Also, individuals with an abdominal adiposity component of MetS showed higher levels of sTfR, although sTfR presented no significant difference between participants with or without MetS in the population based case control study [7].…”
Section: Discussionmentioning
confidence: 91%
“…The fifteen studies found [11-22,26,31,32] were published between 2004 and February 2014. One study was performed in the United States [11], nine studies in Asia [13,15-18,20,22,26,31]; four in Europe [12,14,21,32] and one in Chile [19]. The number of subjects per study varied between 155 [19] to 13,084 [26] (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The second hypothesis would be that moderately elevated transferrin could lead to METS through multiple complex mechanisms [10,15,19]. The first mechanism implies the excessive formation of reactive oxygen species (ROS) from peroxide reactions combined with the inhibition of antioxidative defenses such as Superoxide Dismutase 2 [10].…”
Section: Physiopathologymentioning
confidence: 99%
“…Indeed, one third of patients with METS present with dysmetabolic iron overload syndrome, a condition characterized by altered regulation of iron transport, hepatic steatosis, insulin resistance, and subclinical inflammation (for a review, see [20]). Thus, transferrin-related increase in ROS levels could lead to an up regulation of gluconeogenesis and to impaired lipid metabolism, two components of METS [10,19,21]. The action of ROS on circulating insulin could increase insulin resistance [10], while vessel damage due to ROS could induce both high blood pressure and atherosclerosis [22] Overall, it remains to be clarified whether METS leads to higher levels of markers of iron metabolism or whether higher levels of markers of iron metabolism lead to METS.…”
Section: Physiopathologymentioning
confidence: 99%